2012
DOI: 10.1093/jat/bks024
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Xylazine, Free Morphine, Codeine, 6-Acetylmorphine, Cocaine and Benzoylecgonine in Postmortem Blood by UPLC-MS-MS

Abstract: Xylazine, a veterinary sedative, has been found as an adulterant of heroin in street drugs in Puerto Rico. It was found in combination with free morphine and 6-acetylmorphine, codeine, cocaine and benzoylecgonine in postmortem cases at the Puerto Rico Institute of Forensic Sciences (PRIFS). Xylazine is not approved for human use because it has been proven harmful. Currently, three separate analyses are required to determine all the aforementioned drugs at the PRIFS's toxicology laboratory. To reduce analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…As xylazine is substituting heroin as a drug of abuse and also been the main adulterant of heroin, the current mixture modality is now among cocaine and xylazine or a mixture of cocaine, xylazine and heroin. This information was obtained from the chemical analysis of seized drug, performed by the Controlled Substance Section at the Puerto Rico Institute of Forensic Science (PRIFS) [13]. …”
Section: Introductionmentioning
confidence: 99%
“…As xylazine is substituting heroin as a drug of abuse and also been the main adulterant of heroin, the current mixture modality is now among cocaine and xylazine or a mixture of cocaine, xylazine and heroin. This information was obtained from the chemical analysis of seized drug, performed by the Controlled Substance Section at the Puerto Rico Institute of Forensic Science (PRIFS) [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Most xylazine LC-MS/MS methods rely on the lighter product ion (m/z 89.7) for quantitation of XYL [6,9,10,13] or the precursor ion (m/z 221) alone [1,8]. However, the current study indicates that sensitivity for XYL can be improved by approximately 40% by using both m/z 89.7 (XYL1) and 163.7 (XYL2) product ions cumulatively.…”
Section: Ms Conditionsmentioning
confidence: 66%
“…The instrumental LLoQ for DMA was 0.2 ng/mL (2 pg on-column) on the LC-MS/MS and 0.4 ng/mL in the original, untreated plasma. In a study using human blood, the reported LLoQ for XYL was 10 ng/mL in blood, which equates to 100 pg on-column [10], and included a 2.5-fold concentration step during the extraction process. We speculate that this 200-fold difference in XYL LLoQs between methods may in part be due to the low organic solvent concentration, and the very short run time (2.5 mins) in the literature method, resulting in matrix suppression of the analyte.…”
Section: Calibration Recovery Validation and Lloqmentioning
confidence: 99%
See 2 more Smart Citations